UPAYA PENINGKATAN PRODUKSI KACANG TANAH (Arachis hipogaea L.) DENGAN APLIKASI MACAM DOSIS SP-36 DAN PUPUK ORGANIK - Muhammad Imam Aminuddin; Isnaini Wahyu Nur Khasanah; Ana Amiroh (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2021)
One of the problems in peanut cultivation is decreasing soil fertility. This is due to the very low soil organic matter content. The effort made is by adding organic fertilizer to the soil and paying attention to the use of fertilizer dosage sp36. The purpose of this study was to determine the effect of organic fertilizer and fertilizer dosage sp-36 on the growth and production of peanut plants. This research was conducted in February-April 2021 in Takerharjo Village, Solokuro District, Lamongan Regency. This study used a factorial randomized block design method with two treatment factors, namely the dose of fertilizer sp-36 and organic fertilizer. The first factor consists of 3 levels, namely: 100, 200 and 300 kg / ha. The second factor consists of 3 levels, namely: no organic fertilizers, chicken manure and rice husks. The observed parameters observed included plant height, number of leaves, weight of wet stover, number of pods per plant, weight of pods per plant and weight of seeds per plot.The results of the study showed that the combination of organic chicken manure treatment and a dose of 200 kg/ha of sp-36 fertilizer had a significant effect on the growth and yield of peanut plants